Pendampingan Usaha Minuman Smoothies Time Mahasiswa Universitas Kristen Toraja - Lisa Kurniasari Wibisono; Helba Rundupadang; Agustinus Mantong; Randi Tangdialla; Althon K. Pongtuluran (Nusantara Mengabdi Kepada Negeri, 2024)
Indonesia is a tropical country, therefore cold and sweet drinks are a favorite sought after by the market. This activity aims to introduce smoothies times products directly to the public. In addition, to remind people to live healthy by consuming smoothies. The peculiarities of the entire Time Smoothies product include the raw material, namely fruit. The fruit that is the main ingredient of the product is fresh fruit and without preservatives so that the quality of the drink will be guaranteed